2013
DOI: 10.1111/1471-0528.12460
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating PETCT in routine surveillance and follow‐up after treatment for cervical cancer: a cost‐effectiveness analysis

Abstract: Objective To undertake a cost-effectiveness analysis that compares positron emission tomography -computed tomography (PET-CT) imaging plus standard practice with standard practice alone in the diagnosis of recurrent or persistent cervical cancer during routine surveillance and follow-up of women who have previously been diagnosed and treated.Design Model-based economic evaluation using data from a systematic review, supplemented with data from other sources, and taking a UK National Health Service (NHS) perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 18 publications
0
18
0
4
Order By: Relevance
“…Twenty-four articles did not report any discount rate for future costs and health outcomes. Five papers [18,20,23,38,40] applied a discount rate to costs only (i.e., either 3.0 or 3.5%). In nine articles, costs and effects were discounted at the same rate (i.e., 3.0% in eight cases, 5.0% in one).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four articles did not report any discount rate for future costs and health outcomes. Five papers [18,20,23,38,40] applied a discount rate to costs only (i.e., either 3.0 or 3.5%). In nine articles, costs and effects were discounted at the same rate (i.e., 3.0% in eight cases, 5.0% in one).…”
Section: Resultsmentioning
confidence: 99%
“…In five cases [18,22,27,32,45], one or more diagnostic tests were added to routine surveillance (e.g., PET-CT imaging plus standard practice). All these papers concluded that a less-intensive follow-up program was clinically and economically justified for a variety of malignancies (i.e., breast, cervical and colorectal cancer and melanoma).…”
Section: Study Findingsmentioning
confidence: 99%
“…Performing routine surveillance 18 F-FDG PET/CT was not cost-effective and had no significant impact on management. The minimal impact on management could be due to lead time bias, and if those patients could get a clinical follow-up, the tumor recurrence would become symptomatic or detected using conventional imaging in several weeks (10,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…60% predicted disease-free survival and 49 another study reported a limited NPV with 21% of patients with CMR on post-treatment FDG PET-CT developing disease recurrence during the median 28-month follow-up, 53 with tumour size and stage acting as predictors for recurrent disease. Furthermore, a systematic review suggests that although more accurate than MRI, PET-CT is less cost-effective in post-treatment surveillance 54 than standard follow-up. Therefore, whilst PET-CT offers promise in post-treatment assessment of cervical cancer, its potential to add value to the treatment pathway remains to be fully realized.…”
Section: Emerging Applications Of Fdg Positron Emission Tomography-ctmentioning
confidence: 99%